2010
DOI: 10.1002/ange.201000068
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Structure–Activity Relationship of a Protein in Its Aggregated States

Abstract: Gleich und doch sehr verschieden: Je nach den verwendeten chemischen, physikalischen und biologischen Bedingungen bildet ein einziges Protein fünf strukturell verschiedene Aggregate (siehe die Elektronenmikroskopiebilder, Maßstäbe: 500 nm), die alle das Kreuz‐β‐Faltblatt‐Motiv enthalten. Die Aggregate unterscheiden sich in ihrer Affinität zu Adenosin‐5′‐triphosphat, Thioflavin T, DNA und Membranmimetika sowie in ihrem Effekt auf die Zellgängigkeit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…72 This unfavorable statistic for soluble proteins is not likely to apply to amyloids since their structure can amplify a low affinity several-fold through repeat-induced cooperative interactions. 61,66 Conclusion In this synopsis, we have discussed some of the possible peptide folds from which the protein fold universe may have arisen. With our arguments coming out in favor of an amyloid CA fold, there is no obvious reason to definitively exclude the possibility that any of the folds discussed above is the CA fold.…”
Section: Proteins As Genes: An Amyloid Replicator As the First Functimentioning
confidence: 98%
See 2 more Smart Citations
“…72 This unfavorable statistic for soluble proteins is not likely to apply to amyloids since their structure can amplify a low affinity several-fold through repeat-induced cooperative interactions. 61,66 Conclusion In this synopsis, we have discussed some of the possible peptide folds from which the protein fold universe may have arisen. With our arguments coming out in favor of an amyloid CA fold, there is no obvious reason to definitively exclude the possibility that any of the folds discussed above is the CA fold.…”
Section: Proteins As Genes: An Amyloid Replicator As the First Functimentioning
confidence: 98%
“…43,61 Interestingly, several studies have shown that there has been an evolutionary selection against β-aggregation-prone In each polymorph, the Glu side chain (yellow) exists in only one of two favored conformations. As in (a), there is an energy barrier (e.g., steric clashes) that prevents an individual from changing conformation on its own.…”
Section: Proteins As Genes: An Amyloid Replicator As the First Functimentioning
confidence: 99%
See 1 more Smart Citation
“…1a) [1318]. These aggregates are typically disordered or amorphous in structure [19, 20]. Additionally, Hsp104 can directly remodel amyloid and this activity governs prion inheritance in yeast (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Protein aggregates display a remarkable structural variability, as seen in electron microscopy, depending on the nature of the involved protein and the stress conditions causing protein aggregation (Kawai-Noma et al, 2010;Wang et al, 2010). Heat-shock induced protein aggregates display a rather disordered or amorphous structure, potentially caused by the co-aggregation of a large diversity of differently misfolded protein species (Tyedmers et al, 2010).…”
Section: Introductionmentioning
confidence: 99%